Perkembangan Akuntansi Syariah - Nur Alfaeni, Vivi; Diana, Nana (CV. Lafadz Jaya, 2023)
The introduction of sharia accounting which cannot be separated from the progress of Islam and the need for non-cash business records is discussed in this note. Al-Baqarah: 282 developed the habit of recording among the community and inspired Muslims to pay attention to registration, which became one of the factors that encouraged cooperation at that time. The term